Potential Seeding From Fine-Needle Aspiration of an Axial Osteosarcoma: A Case Report - Faletti, Tasha; Seguin, Bernard; Selmic, Laura Elizabeth; Lapsley, Janis; Worley, Deanna; Griffin, Maureen; Tremolada, Giovanni (Frontiers in Veterinary Science, 2022)
The present report describes the first potential case of seeding after a fine needle aspiration (FNA) of a rib osteosarcoma in a dog. An 8-year-old, 28-kg, female spayed Golden Retriever was presented to its primary veterinarian with a 3-week history of a 3cm firm, non-painful, immobile mass arising from the 9th rib. The mass was aspirated and submitted for cytological examination. A subcutaneous nodule developed several days after the FNA was performed in a location immediately overlying, but distinct from the primary rib tumour on palpation. Both the primary mass and the newly diagnosed subcutaneous nodule were biopsied and were consistent with an osteosarcoma. Although it cannot be ruled out that the subcutaneous lesion was metastatic, seeding was a reasonable explanation based on where the new mass was located and how quickly appeared after the FNA was performed. The aim of this case report was to describe the possibility of tumour seeding during FNA for osteosarcoma. It is the authors’ opinion that utility of cytological diagnosis of bone tumours outweighs the risk of possible seeding and should continue to be used as a routine diagnostic test for the diagnosis of aggressive bone lesions.